Eating contexts determine the efficacy of nutrient warning labels to promote healthy food choices - Caballero, Sara; Moënne-Loccoz, Cristóbal; Delgado, Mauricio; Luarte, Luis; Jimenez, Yanireth; Galgani, José E.; Perez-Leighton, Claudio E. (Frontiers in Nutrition, 2023)
Unhealthy food choices increase the risk of obesity and its co-morbidities. Nutrition labels are a public health policy that aims to drive individuals towards healthier food choices. Chile has been an example of this policy, where mandatory nutrient warning labels (NWL) identify processed foods high in calories and critical nutrients. Eating contexts influence individual food choices, but whether eating contexts also influence how NWL alter the decision process and selection during food choice is unknown. In an online mouse-tracking study, participants prompted to health, typical, or unrestricted eating contexts were instructed to choose between pairs of foods in the presence or absence of NWL. Conflict during choices was analyzed using mouse paths and reaction times. We show that NWL increased conflict during unhealthy food choices and reduced conflict during healthy choices in all contexts. However, the probability that NWL reversed an unhealthy choice was 80% in a healthy, 37% in a typical, and 19% in an unrestricted context. A drift-diffusion model analysis showed the effects of NWL on choice were associated with an increased bias towards healthier foods in the healthy and typical but not in the unrestricted context. Our study suggests that the efficacy of NWL to drive healthy food choices increases in healthy eating context, whereas NWL are less effective in typical or unrestricted eating contexts.